User adoption and use of e-government online service / Mas Anom Abdul Rashid and Mohd Noor Azman Othman - Abdul Rashid, Mas Anom; Othman, Mohd Noor Azman (Universiti Teknologi MARA Cawangan Pahang, 2010)
There is evidence of a universal shift toward modern online public services. Governments and public sector organ-izations around the globe have to take notice of this phenomenon, becoming aware of its potentials and incorporat-ing information technology in delivering better services to the public via e-government. The prime aim of e-government in Malaysia is to serve the 'rakyat' (citizen) and to have better online service. Although it is clear that citizen is the main user of e-government online services, there are only few studies conducted on the issue of citizen adoption of the online service. This paper presents the level of citizen adoption as one of the perspectives of e-government implementation. The model is built on the Technology Adoption Model (TAM) and Technology Plan-ning Behaviour (TPB) and literature related to these models.